SISMED: um sistema de controle de consultório médico - Santos, Wesley Adamo Costa dos (Universidade Federal Rural do Semi-Árido, 2019)
Advances of the Internet, especially in the last decades, made the services available more and more present in people's lives. For this, applications are created in order to support the most diverse activities, between labor, academic or personal. This importance is justified by the advantages provided, namely: practicality, means of communication and information, ECommerce. Among the services, the Web stands out. The objective of this work is to demonstrate the creation of a Web system for the control of a doctor's office. Based on the need for a web system for Universidade Federal Rural do Semi-Árido - UFERSA's medical practice, the production of this work was verified. For that, prototyping was used with the UFERSA medical professor in order to raise the necessary requirements for the development of the application. In addition, the JAVA development platform was chosen along with the agile development methodology eXtreme Programming (XP). With this work, the medical practice professionals provide a support tool for patient care and office management, and provides medical students, guided by teachers, the practice of the knowledge acquired during the course through care to the patient supported by the developed system.
Monografia
Keywords: Internet; Sistema web; Medicina; Consultório médico; Internet; Web system; Medicine; Doctor'soffice; ENGENHARIAS::ENGENHARIA DE COMPUTACAO